Parents’ Perceptions of School Excellence - Wasal Khan; Mohammad Iqbal (International Conference on Education and Language (ICEL), 2013)
The education system of Pakistan, in general, and Khyber Pakhtunkhwa, in particular, suffers from deterioration. Most of the schools in Khyber Pakhtunkhwa direly need improvement. Turning schools into Centres of Excellence requires exploration of factors that couldlead them to excellence.According to Sergiovanni (1983) excellence is identified with effective schools which, like other human enterprises, grow over a period of time, through persistent efforts for changing conditions; painstaking approaches for maintaining the complex processes and relationship within and outside the schools. Research has documented that attempting to improve the quality of personal relationships among stakeholders was instrumental to better school climate, staff morale, and public confidence in schooling.The current study was carried out in boys’ secondary schools located in Khyber Pakhtunkhwa, Pakistan. The population of the study included all the parents whose children were studying in those schools. It was also because parents were considered more important stakeholders in schooling of their children. The sample comprised 60 parents purposively selectedproportionately of 30 sampled boys’ high schools (26 from private sector and 4 from public sector).Interviews with parents were used as major instrument for collection of data. Those were held with purposively selected respondents whose children were in 10th class of each sampled school. The interview items were of multi-dimensional nature.The data were given both quantitative and qualitative treatment. The outcome of the study revealed a number of factors based on parents’ responses and expectations that could help convert a school into a centre of excellence.